Analysis Of Factors Related to The Incidence of Stunting Toddlers in The Region Gambah Health Center - Dewi, Nanda Citra; Haryono, Ika Avrilina; Salmarini, Desilestia Dwi (Fakultas Ilmu Kesehatan, 2024)
Stunting is a condition of growth failure that occurs in toddlers. The 2022 SSGI survey results show that stunting in Indonesia is at 21.6%. Data from the South Kalimantan Provincial Health Office in 2022 indicates a rate of 24.6%. Data from the HSS Health Office in 2022 shows a rate of 4.53%. Among the 21 Health Centers in the HSS area, the Gambah Health Center ranks first with the highest stunting rate at 11.60%. Stunting is not caused by a single factor but by multiple factors. The aim of this research is to analyze the factors associated with the incidence of stunting in toddlers. This research is a quantitative analysis using a case-control study method. The study employs chi-square tests and odds ratios. The sample consists of 120 toddlers, with 40 cases and 80 controls. The results of this study indicate that the factors associated with the incidence of stunting in toddlers are birth weight (p-value 0.022, OR 3.381), exclusive breastfeeding (p-value 0.000, OR 5.741), mother's education level (p-value 0.015, OR 5.444), history of pregnancy age (p-value 0.000, OR 9.736), and maternal nutritional status (p-value 0.006, OR 8.273). The conclusion of the research birth weight, exclusive breastfeeding, mother's education level, history of pregnancy age, and maternal nutritional status are factors that can cause the incidence of stunting in toddlers.